Rabbit Race - "Daniels, Lucy" (Hodder Children's Books: London, 1996)
Jack's dog has just died and he needs cheering up. Mandy thinks a new pet will help... This title is part of the "Animal Ark" series that provides animal stories for younger readers.
Keywords: Animal Ark